Pemanfaatan Media Massa Dalam Melestarikan Tenun Ikat Di Era Teknologi Moderen di Desa Werangggere, Kabupaten Flores Timur - Elvera Rosa Ina Dai Wahon; Marianus Kleden; Stephanie P A Lawallu (Universitas Kristen Indonesia Toraja, 2024)
Ikat weaving is a culture that is very thick with the meaning and value contained in each distinctive motif produced in the form of nowing and kwetek fabrics worn by men and women in everyday life both customary traditions that have been left by ancestors. Crafts made by weaving craftsmen in Weranggere Village are no less interesting than woven fabric craftsmen from other villages. However, there are problems that I encountered at the MBKM location, namely that there is no marketing or selling out of the area. They only sell it in the market or around the village or neighboring villages. As we all know that in today's technological age, it is very necessary for business methods to be carried out through the use of technology in the form of using social media. The purpose of that is so that how to introduce social media to mothers in promoting woven ikat fabrics in the modern era without having to sell in the market. So that woven fabrics are not only known in the East Flores region but also at the national and international level